Circular RNA: a new star in neurological diseases. (3rd August 2017) - Li, Tao-Ran; Jia, Yan-Jie; Wang, Qun; Shao, Xiao-Qiu; Lv, Rui-Juan
Abstract : Circular RNAs (circRNAs) are novel endogenous non-coding RNAs characterized by the presence of a covalent bond linking the 3' and 5' ends generated by backsplicing. In this review, we summarize a number of the latest theories regarding the biogenesis, properties and functions of circRNAs. Specifically, we focus on the advancing characteristics and functions of circRNAs in the brain and neurological diseases. CircRNAs exhibit the characteristics of species conservation, abundance and tissue/developmental-stage-specific expression in the brain. We also describe the relationship between circRNAs and several neurological diseases and highlight their functions in neurological diseases.